KONTRIBUSI CORPORATE SOCIAL RESPONSIBILITY (CSR) MELALUI PROGRAM INTEGRATED COMMUNITY DEVELOPMENT (ICD) TERHADAP KEHIDUPAN MASYARAKAT (Studi Kasus PT. Tirta Investama (Aqua) di Desa Karangjati Kecamatan Pandaan Kabupaten Pasuruan) - Syaifuddin Fahmi, Didik Prasetyo V (Program Studi Ekonomi Syariah Universitas Yudharta Pasuruan, 2018)
This research is donedue to there is still social gap in particularly of early childhood education field, economic and environmental issues.This research has used the descriptive research with qualitative method. The research has purposed to know, to describe and to analyze the contribution of Corporate Social Responsibility (CSR) PT. Tirta Investama Pandaan Factory inpenetrate of Integrated Community Development (ICD) program on community life in Karangjati village, Pandaan district, Pasuruan city. This research was conducted at PT. TIRTA INVESTAMA PANDAAN by initiating research on October 2thtill December 20th 2017. From this research it can be concluded that the planned of CSR program is almost entirely implemented. But in the implementation there are still deficiencies so that the results of the implementation of the program has not been maximized yet. Of these shortcomings can be given a recommendation that requires a clear measurement and reporting so that information obtained can be used as an evaluation for the implementation of the next program.